Comparison of the accuracy of body temperature measurements with temporal artery thermometer and axillary mercury thermometer in term newborns - Markus Gunawan; Soetjiningsih Soetjiningsih; I Made Kardana (Paediatrica Indonesiana, 2010)
AbstractBackground Rectal mercury thermometer (RT) has beenconsidered to be a clinical thermometer that measures bodytemperature close to core temperature. Unfortunately it is relativelyuncomfortable to the patient. Axillary mercury thermometer (AT)is a relatively safe method, but time consuming and its accuracyhas been questioned. Temporal artery thermometer (TAT) isrelatively a new method that can measure body temperaturefaster, and well tolerated.Objective To compare the accuracy of temperature measurementbetween TAT and AT in neonates.Methods Cross-sectional analytic study was conducted atNeonatology Division at Sanglah Hospital, Denpasar. Every healthyterm newborn who met the criteria were measured their bodytemperature by using three kinds of thermometer consecutively. Thelimits of agreement, correlation and linear regression analysis weredone to find TAT and ATâ€™s agreement and correlation to RT.Results One hundred and thirty four newborns were enrolledin this study. TAT had a better agreement to RT with the meanô€‡ô€Œô€‰ô€‰ô€ˆô€•ô€ˆô€‘ô€†ô€ˆô€€ƒô€’ô€‰ô€€ƒô€€ô€€“ô€€‘ô€€“ô€€”ô€‚žô€€¦ô€€ƒô€šô€Œô€—ô€‹ô€€ƒô€€•ô€€ƒô€€¶ô€€§ô€€ƒô€ô€’ô€šô€ˆô€•ô€€ƒô€ô€Œô€ô€Œô€—ô€€ƒô€’ô€‰ô€€ƒô€€ô€€“ô€€‘ô€€•ô€€™ô€‚žô€€¦ô€€ƒô€„ô€‘ô€‡ô€€ƒô€˜ô€“ô€“ô€ˆô€•ô€€ƒô€ô€Œô€ô€Œô€—ô€€ƒô€’ô€‰ô€€ƒô€€“ô€€‘ô€€•ô€€–ô€‚žô€€¦ô€€ô€€ƒô€†ô€’ô€ô€“ô€„ô€•ô€ˆô€‡ô€€ƒô€—ô€’ô€€ƒô€„ô€Šô€•ô€ˆô€ˆô€ô€ˆô€‘ô€—ô€€ƒô€…ô€ˆô€—ô€šô€ˆô€ˆô€‘ô€€ƒô€€¤ô€€·ô€€ƒô€„ô€‘ô€‡ô€€ƒô€€µô€€·ô€€ô€€ƒô€šô€Œô€—ô€‹ô€€ƒô€ô€ˆô€„ô€‘ô€€ƒô€‡ô€Œô€‰ô€‰ô€ˆô€•ô€ˆô€‘ô€†ô€ˆô€€ƒô€€ô€€“ô€€‘ô€€–ô€€˜ô€‚žô€€¦ô€€ô€€ƒô€€•ô€€ƒô€€¶ô€€§ô€€ƒô€ô€’ô€šô€ˆô€•ô€€ƒô€ô€Œô€ô€Œô€—ô€€ƒô€€ô€€“ô€€‘ô€€šô€€“ô€‚žô€€¦ô€€ƒô€„ô€‘ô€‡ô€€ƒô€˜ô€“ô€“ô€ˆô€•ô€€ƒô€ô€Œô€ô€Œô€—ô€€ƒô€’ô€‰ô€€ƒô€€“ô€€‘ô€€“ô€€“ô€‚žô€€¦ô€€‘ô€€ƒô€€·ô€‹ô€ˆô€•ô€ˆô€€ƒô€šô€„ô€–ô€€ƒô€„ô€€ƒô€–ô€Œô€Šô€‘ô€Œô€‰ô€Œô€†ô€„ô€‘ô€—ô€€ƒô€ô€Œô€‘ô€ˆô€„ô€•ô€€ƒô€„ô€–ô€–ô€’ô€†ô€Œô€„ô€—ô€Œô€’ô€‘ô€€ƒô€…ô€ˆô€—ô€šô€ˆô€ˆô€‘ô€€ƒô€€·ô€€¤ô€€·ô€€ƒand RT with correlation coefficient ô€•ô€€ƒô€€ ô€€ƒô€€“ô€€‘ô€€›ô€€šô€€ƒô€€‹ô€“ô€€Ÿô€€“ô€€‘ô€€“ô€€“ô€€”ô€€Œô€€ô€€ƒô€Œô€‘ô€—ô€ˆô€•ô€†ô€ˆô€“ô€—ô€€ƒô€€“ô€€‘ô€€œô€€›ô€€šô€€ƒô€„ô€‘ô€‡ô€€ƒô€–ô€ô€’ô€“ô€ˆô€€ƒô€€“ô€€‘ô€€˜ô€€“ô€€œô€€‘ô€€ƒô€€·ô€‹ô€ˆô€€ƒô€ô€Œô€‘ô€ˆô€„ô€•ô€€ƒô€„ô€–ô€–ô€’ô€†ô€Œô€„ô€—ô€Œô€’ô€‘ô€€ƒô€…ô€ˆô€—ô€šô€ˆô€ˆô€‘ô€€ƒô€€¤ô€€·ô€€ƒô€„ô€‘ô€‡ô€€ƒô€€µô€€·ô€€ƒô€–ô€‹ô€’ô€šô€ˆô€‡ô€€ƒô€—ô€‹ô€ˆô€€ƒô€†ô€’ô€•ô€•ô€ˆô€ô€„ô€—ô€Œô€’ô€‘ô€€ƒô€†ô€’ô€ˆô€‰ô€‰ô€Œô€†ô€Œô€ˆô€‘ô€—ô€€ƒô€•ô€€ƒô€€ ô€€ƒô€€“ô€€‘ô€€šô€€™ô€€ƒô€€‹ô€“ô€€Ÿô€€“ô€€‘ô€€“ô€€“ô€€”ô€€Œô€€ô€€ƒô€Œô€‘ô€—ô€ˆô€•ô€†ô€ˆô€“ô€—ô€€ƒô€€”ô€€“ô€€ô€€•ô€€šô€€”ô€€ƒô€‡ô€„ô€‘ô€€ƒô€–ô€ô€’ô€“ô€ˆô€€ƒô€€“ô€€ô€€šô€€–ô€€“ô€€‘Conclusion TAT is more accurate than AT for body temperaturemeasurement in the healthy term newborns. [Paediatr Indones.2010;50:67-72].